2004
DOI: 10.1007/s10342-004-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics and biomass accumulation of 8-year-old hybrid poplar clones in a short-rotation plantation on a clayey-sandy mining substrate with respect to plant nutrition and water budget

Abstract: In 1995 a short-rotation plantation (2.5 ha) was established in the mining region Welzow-Su¨d in Brandenburg, Germany, on a clayey-sandy, lignite-and pyrite-free substrate in order to study the biomass potentials of fast-growing tree species (hybrid poplar clones). In this study, special emphasis was placed on yield aspects as well as on the interaction between soil and plants, especially with regard to the plant nutrition and soil-water relationships. So far, the results indicate that the cultivation of hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
2
43
0
2
Order By: Relevance
“…The cultivation of fast-growing tree species for soil remediation and the production of renewable energy from contaminated biomass is an alternative approach to more traditional types of land use of post-mining polluted areas [1][2][3][4]. In this context, compared to herbaceous species, fast-growing trees have several advantages, such as a deeper root system, high productivity and transpiration activity.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of fast-growing tree species for soil remediation and the production of renewable energy from contaminated biomass is an alternative approach to more traditional types of land use of post-mining polluted areas [1][2][3][4]. In this context, compared to herbaceous species, fast-growing trees have several advantages, such as a deeper root system, high productivity and transpiration activity.…”
Section: Introductionmentioning
confidence: 99%
“…24 t/ha (respectiv 13 t/ha după 4 ani și 18 t/ha după 5 ani). În studiul respectiv, clona Max4 obține cele mai slabe rezultate față de restul clonelor ce s-au testat (Bungart & Hüttl 2004).…”
Section: Biomasa Clonelorunclassified
“…Further investigations showed that clones with higher shoot hydraulic conductivity and transpiration rate had significantly higher yields (Bungart et al 2000). Cultivation of hybrid poplar (Populus) clones in a short-rotation plantation was an adequate tool for establishing alternative land use systems in the Lusatian post-mining landscape as a potential source of biomass energy (Bungart and Hu¨ttl 2004).…”
Section: Agroforestry Recultivationmentioning
confidence: 99%